Charge asymmetries for D, Ds and [lambda]c production in [sigma]- -nuleus interactions at 340 GeV/c - Adamovič, M. I.; Siebert, Hans-Wolfgang (The European physical journal. C, Particles and fields, 1999)
CERN experiment WA89 has studied charmed particles produced by a Σ−Σ−Σ^- beam at 340 GeV/c on nuclear targets. Production of particles which have light quarks in common with the beam is compared to production of those which do not. Considerable production asymmetries between D−D−D^- and D+D+D^+, D−sDs−D_s^- and D+sDs+D_s^+ and ΛcΛcΛ_\mathrm c and Λc¯Λc¯\bar{Λ_\mathrm c} are observed. The results are compared with pion beam data and with theoretical calculations.
Im Titel werden Lambda und Sigma als griechische Buchstaben dargestellt
Im Titel sind s und c tiefgestellt
Im Titel ist bei "Sigma minus" das Minuszeichen hochgestellt
Gesehen am 27.02.2020